Family Resilience and Social Transformation in West Nusa Tenggara: Exploring Adaptive Capacities in Changing Communities - Sambirang Ahmadi; Nikmatullah; Dahlia Hidayati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Family resilience is a fundamental element in maintaining social stability, improving community welfare, and supporting sustainable development. In the context of West Nusa Tenggara (NTB), family resilience has unique characteristics shaped by the interaction of religious values, local culture, and socio-economic conditions. This study aims to analyze the dynamics of family resilience in NTB, identify the challenges faced by families, and formulate strategies for strengthening family resilience based on local contexts. This study employed a qualitative descriptive approach through literature review and secondary data analysis from the National Population and Family Planning Agency (BKKBN) and Statistics Indonesia (BPS). The findings indicate that families in NTB possess strong social and spiritual capital reflected in religious commitment, family values, and community solidarity. However, family resilience remains challenged by economic vulnerability, educational disparities, and limited access to reproductive health information. Therefore, strengthening family resilience in NTB requires an integrated strategy through family economic empowerment, improvement of educational and digital literacy, and revitalization of religious values and local cultural practices that support family functions. This study contributes to understanding family resilience from a regional perspective by emphasizing the importance of socio-cultural and structural factors in building strong and adaptive families.